MORAL VALUES IN ADOLESCENTS: THE FORCE OF AFFECTIONS IN CONTEMPORARY TIMES - Bergamo Braga, Maria Cecilia [UNESP]; Martins, Raul Aragao [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2020)
The way members of a society interact with each other shows how they see each other and understanding these interactions is an important element of educational work. In this perspective, this study proposes a theoretical discussion on concepts related to the theme of morals and ethics, and the empirical investigation of a possible relationship between positive self-representation and the socio-moral perspective of high school students. The theoretical basis of the work rests on Piaget and Kohlberg's studies on moral development. In order to achieve these goals, it was investigated how students adhere to the moral values of justice, solidarity, respect and democratic coexistence and what representation of themselves they have. 122 students from two schools were investigated, one religiously oriented and one public. The schools are located in two cities in the northwest of Sao Paulo state, Brazil. Students answered the Moral Values Scale and two questions about self-representation. The application of the instruments was performed collectively in the students' own classroom. The results pointed to a mostly sociocentric characterization of the students and for affirmative matches between some profile data, positive self-representation, and better levels of moral response.
Keywords: Moral values; ethic; representation of themselves; teenagers